Accounting practices and performance of Small Medium Enterprises - Nalubowa Irene (UCU, 2024)
The purpose of this study was to investigate the relationship between accounting practices and the performance of Small medium enterprises in the study context. SMEs are recognized as essential contributors to essential contributors to economic development. Despite their importance, they face challenges therefore the study explored how the accounting practices can improve SMEs providing actionable insights for business owners, policy makers and other stakeholders. The study was guided by three objectives which included: to examine the role of book keeping in performance of small medium enterprises in the study context, to examine the role of budgeting on to performance of small medium enterprises in the study context, to examine the role of financial reporting in the performance of small medium enterprises in the study context. The research employees across sectional survey design and gather qualitative data. The study population comprises of 60 respondents with a sample size of 52. A structured questionnaire was used to collect primary data on accounting practices employed by these businesses and their impact on performance indicators such as profitability, sales growth and overall business sustainability Key findings revealed a strong positive relationship between accounting practices and SMEs performance. Respondents agreed that proper bookkeeping enhances financial accuracy, facilitates better debt management, and enhances budgeting and financial forecasting all of which contribute to improve financial decision making. Effective budgeting was found to help SMEs set realistic profitability targets, allocate resources efficiently, and manage financial risks. Financial reporting was found to improve transparency, stakeholder confidence, and decision-making processes, contributing to the overall growth and sustainability of SMEs. The study emphasizes the significance of adopting reliable and ethical research practices, including expert-reviewed questionnaires and adherence to confidentiality and informed consent. This research provides valuable insights into how sound accounting practices can drive SMEs performance and long term success. These include the need for SMEs to invest in professional accounting services, implement formal budgeting processes and adopt digital tools for bookkeeping and financial reporting. These measures would not only improve operational efficiency but also increase profitability and long term sustainability
Dissertation